2016
DOI: 10.7314/apjcp.2016.17.3.1149
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy Examination for Breast Cancer in a Routine Laboratory Practice: Results of a Pilot Study

Abstract: Background: Examination of sentinel lymph node (SLN) biopsies provides accurate nodal staging for breast cancer and plays a key role in patient management. Procurement of SLNs and the methods used to process specimens are equally important. Increasing the level of detail in histopathological examination of SLNs increases detection of metastatic tumours but will also increase the burden of busy laboratories and thus may not be carried out routinely. Recommendation of a reasonable standard in SLN examination is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…At the same time, studies have shown a need for thorough examination of all axillary SLNs in an attempt to eradicate any false-negative assessments, which only adds to the growing workload of pathologists and today's laboratories. 13,16 As a consequence, many laboratories have abandoned frozen section examination of SLNBs. 17 Standardization of tissue processing, IHC staining and optimal assessment with cost-effective methods for histopathological examination of SLNs is therefore necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, studies have shown a need for thorough examination of all axillary SLNs in an attempt to eradicate any false-negative assessments, which only adds to the growing workload of pathologists and today's laboratories. 13,16 As a consequence, many laboratories have abandoned frozen section examination of SLNBs. 17 Standardization of tissue processing, IHC staining and optimal assessment with cost-effective methods for histopathological examination of SLNs is therefore necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The SLNB technique introduces serial sectioning of SLNBs, in which up to nine SLNs and an average of two SLNs per patient have to be examined. At the same time, studies have shown a need for thorough examination of all axillary SLNs in an attempt to eradicate any false‐negative assessments, which only adds to the growing workload of pathologists and today's laboratories . As a consequence, many laboratories have abandoned frozen section examination of SLNBs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the 6 th edition of International Union Against Cancer (UICC), lymph node metastasis (LNM) is classified into isolated tumor cells (ITC), micrometastasis (MI), and macrometastasis (MA), depending on the size of the metastatic deposit (5). Methods to investigate the presence of MI vary, from serial slices with hematoxylin and eosin (H&E) staining, immunohistochemical (IHC) staining, to real-time reverse transcription-polymerase chain reaction (RT-PCR) (6)(7)(8)(9). Cytokeratin is one component of the cytoskeleton of epithelial cells that is not present in normal lymph nodes, and its corresponding antibody is widely used to detect minute deposits of tumor cells in lymph nodes by IHC staining.…”
Section: Introductionmentioning
confidence: 99%